Γ-Glutamyl-dipeptides: Easy tools to rapidly probe the stereoelectronic properties of the ionotropic glutamate receptor binding pocket. Issue 51 (22nd December 2016) - Tamborini, Lucia; Nicosia, Veronica; Conti, Paola; Dall'Oglio, Federica; De Micheli, Carlo; Nielsen, Birgitte; Jensen, Anders A.; Pickering, Darryl S.; Pinto, Andrea
Abstract: γ-Glutamyl-dipeptides, built by condensing the distal carboxylate of l -Glu (or d -Glu) onto a series of differently functionalized amino acids, were prepared and used as tools for rapidly probing the stereo-electronic properties of iGluRs, searching for subtype-selective ligands. Graphical abstract: